PENGARUH KETAHANAN DAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH PERILAKU KEWARGAAN ORGANISASIONAL PADA KARYAWAN DI HARIAN SERAMBI INDONESIA - Fadli Ferdiansyah; Irma Suryani (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study shows that the Effect of Resilience and Perceived Organizational Support related to Employee Performance mediated by Organizational Citizenship Behavior on Employees at Harian Serambi Indonesia. Therefore, this study provides literature on the contribution to resilience, perceived organizational support and work performance through the mediating role of organizational citizenship behavior. The sampling technique used is saturated sampling (census). This study uses Hierarchical Linear Modeling (HLM) as an analytical method to determine the effect of the variables involved. Based on the results of the HML that resilience has an effect on employee performance. Perception of Organizational Support has an effect on Employee Performance. Resilience affects Organizational Citizenship Behavior. Perception of Organizational Support has an effect on Organizational Citizenship Behavior. Organizational Citizenship Behavior has an effect on Employee Performance. Resilience affects employee performance through organizational citizenship behavior. Perception of Organizational Support has an effect on Employee Performance through Organizational Citizenship Behavior.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//